The Oxford handbook of organizational identity - Pratt, Michael G.; Schultz, Majken; Ashforth, Blake E.; Ravasi, Davide, 1970- (Oxford handbooks online., 2016)
Identity studies focus on how organisations define themselves and what they stand for in relation to internal and external stakeholders. This handbook offers an introduction to the growing field of organisational identity and a broad range of the most important theories and methods for the study of organisational identity.